Effect of the ball on quickness and acceleration performance in young soccer players - Nurtekin, E.; Taskin, H.; Tunga Peker, A. (Science, Movement & Health, 2013)
The aim of the research. The purposes of this study was to examine the effect of ball on quickness and acceleration performance in young soccer players. Methods of research. A total of 16 soccer players were examined. These soccer players were playing in first leagues of Turkey. The mean (SD) age was 18,19±0,75 years, height was1,82±6,63 m, and weight was 73,5±6,07 kg for the 16 soccer players. While the tests were conducted, the same weather conditions were taken into consideration. This was followed by the administration of 5-m quickness, 5-m quickness with ball, 10-m acceleration, and acceleration with ball tests. Each test was applied twice, with a 3-minute interval, and the best result was recorded. There was a 5-minute rest session between the two tests. Soccer balls, cone, photocell, and tape measure for distance were used. The methodology employed during the tests is summarized in the following paragraphs. Main results. A significant relationship no existed between quickness and quickness wit ball (P>0.05). On the other hand, a significant relationship existed between acceleration and acceleration wit ball (P<0.05). A unit increase in acceleration with ball lead to a change in the rate of 51% in acceleration performance. In conclusion; our study showed that quickness is very important for soccer game. All soccer players need to moves quickly with ball and without ball. Also, to minimize change of speed, coaches should imporove acceleration wit ball in training. Their training should involve in multiple planes at varied speeds.